Advanced Yield Trial for Various Peanut Lines (Arachis hypogaea L.) at Sodonghilir, Tasikmalaya, West Java, Indonesia - Nurhalimah, Siti; Wahyu, Yudiwanti; Nurhidayah, Siti; Firmansyah, Efrin (Department of Agronomy and Horticulture, IPB University, 2021)
This study aims to evaluate yield and yield components in several peanut lines planted in West Java, Indonesia. The genetic materials tested involved 21 genotypes consisting of 18 potential peanut lines (G100, G133, G142, G144, G199, G205, G209, G21, G234, G237, G33, G37, G41, G53, G54, G76, G84, G99) from a selection of 5 biparental population (GWS79A1/”Zebra”, “Jerapah”/GWS79A1, “Zebra”/GWS79A1, GWS79A1/”Jerapah”, “Zebra”/GWS18A1) and 3 comparative varieties (“Gajah”, “Sima”, and “Zebra”) as controls. Results showed that various genotypes have significant effects on plant height (at 9 and 10 WAP), number of branches (at 4, 10, and 12 WAP), flowering age, and harvest age. Some potential lines showed ideal characters expected of a high quality peanut plant. Based on characters such as harvest age, dry pod weight, and productivity, G100, G41, G21, G205, and G84 can be considered the best potential lines. These lines demonstrated high heritability values including characters classified as high category such as plant height, number of branches, age of flowering, age of harvest, harvest index, wet stover weight, fresh pod weight, number of filled pods, number of empty pods, number of filled pods, and weight of 100 seeds. Additionally, these lines also show high productivity, a character classified in the medium category.